Analisis Desain User Interface pada Aplikasi Pencari Parkir Mobil - Arfianto, Muhammad Rizky (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2022)
The rapid population growth has an impact on the increase in the number of vehicles. The problem of parking space needs is a common phenomenon that occurs in Indonesia, many parking systems currently available only record the time of entering and leaving the car and calculating how long the car has been in the parking lot. As the development of increasingly sophisticated technology makes changes in human character to want things that are easy and fast, so is the parking problem that is happening today. In 2019 there is a parking facility application that has the main feature of searching for the nearest parking lot, but the application still does not have complete parking facilities and also a user interface display that still confuses users. A good user interface has aspects of clarity, conciseness, recognizability, responsiveness, consistency and has aesthetic content. Therefore, it is important to design the user interface and usability so that users are more interested and can explore the application and the need for additional features to the application so that the application can have complete features and work well.